The Effect of 3D-Based Educational Games on Literacy Skills in Group B Children - Intisari, Intisari; Hasmawaty, Hasmawaty; Hasbur, Heni Safitri (UIN Sultan Maulana Hasanudin Banten, 2025)
This study aims to determine the effect of the use of 3D-based educational games on early childhood literacy skills, especially in group B at Insan Madani Kindergarten, Ujung Bulu District, Bulukumba Regency. The method used was an experiment with a one-group pretest-posttest design and a qualitative approach. The sample consisted of 17 children aged 5-6 years who were treated using 3D-based educational games during three meetings. Literacy ability data was measured through pretest and posttest, then analyzed using the paired sample t-test. The results showed a significant increase in children's literacy skills with an average pretest score of 23.18 and posttest score of 55.24. Statistical analysis showed a significant difference (p < 0.05) between the pre- and post-treatment values. 3D-based educational games provide an interactive, engaging, and fun learning experience that can optimally improve children's interest and literacy skills. This study concludes that the use of 3D-based educational games is effective as an innovative learning method to develop early childhood literacy skills.